Peculiarities of some law enforcement agencies’s activities: national and foreign experience - K. O. Tokarieva; M. V. Golub (Bulletin of Kharkiv National University of Internal Affairs)
It has been determined that the MIA system reform is aimed at improving and optimising its structure, organising activities with a view to combating crime and corruption, timely detection of collaboration and prevention of threats to Ukraine’s external and internal security, and improving the level of protection of citizens' rights and freedoms and prevention of offences. The goal of this process is to complete the transformation of the MIA system into a law enforcement agency that meets modern European requirements. The peculiarities and current trends in the development of law enforcement systems of the European Union, the USA and Japan in terms of measures aimed at ensuring the proper state of public security and public order have been studied. The principles of municipal police units functioning in Germany, the UK, the USA and Japan have been considered.